Analysis of optimum FBG configurations in DPSK and DQPSK systems - Go, Yun Ii; Thio, Gilbert Tzer Hwai* (IET, 2014)
This paper presents the optimization of fiber Bragg grating (FBG) configurations for systems implemented with two modulation schemes: differential phase shift keying (DPSK) and differential quadrature phase shift keying (DQPSK). This paper investigates the possibility of applying a new FBG configuration based on standard spread spectrum sequences. Phase encoding using FBG is applied in both systems. Two design parameters of the encoding schemes are evaluated: code weight and chip length. The system performance is evaluated from three key aspects: modulation scheme, signal-to-noise ratio (SNR) and transmission distance. A comparative study on different FBG configurations is also outlined. This work eliminates the requirement of wavelength conversion and fiber delay lines (FDL). The optimal solution is evaluated in a four-user system considering various noise sources and non-linear effects.